(untitled) (Research, Society and Development, 2022)
To describe the most prevalent microorganisms in the Intensive Care Unit and the main ‘ factors for patients who need this type of support. This is an integrative literature review, using the Pubmed, Scielo and Virtual Health Library (BVS) databases. The controlled descriptors “hospital infection”, “ICU” and “critical care” were used. Using the Boolean operator “AND”. In the period from 2017 to 2021. As inclusion criteria: primary studies and full article in full that responded to the objective, as exclusion criteria: monographs, case studies; periodicals; incomplete texts. Eight articles were selected at the end of the analysis for the study. It was pointed out that multidrug-resistant gram-negative bacilli were the main microorganisms causing infections in ICUs, namely: Acinetobacter baumannii; Pseudomonas aeruginosa and Enterobacter and Klebsiella. Among the most frequent gram positives are: Staphylococcus epider; Pneumoal Staphylococcus and Enterococcus spp. Among the selected studies, it is observed that the risk factors commonly reported were long-term antimicrobial therapy, length of hospital stay and invasive procedures, age and sex. The most prevalent microorganisms were gram negative bacilli that inhabit the patient’s natural microbiota, which over the years have acquired multi-resistance to the antibiotics most used in clinical practice. Such infections are related to the health services provided. Measures such as hand hygiene and controlled use of antibiotics are still the most effective means of controlling HAIs in the ICU.